Geography of masting creates greater synchrony in seed scarcity than in seed abundance - Jakub Szymkowiak; Jessie J. Foest; Marcin K. Dyderski; Szymon Jastrzȩbowski; Maciej K. Barczyk; Andrew Hacket-Pain; Michał Bogdziewicz (Proceedings of the National Academy of Sciences, 2025)
Interannually highly variable and synchronized production of large seed crops by perennial plants, called masting, drives resource pulses and famines with cascading effects on food webs. While the spatial scale of masting synchrony is well documented, it remains unclear how synchrony differs between years of seed abundance and failure, and how such dynamics extend across species and space. These gaps are important to resolve, as they determine the magnitude and spatial extent of masting effects on food webs. Using a 36-y dataset from 431 sites spanning seven dominant tree species in temperate Europe, we provide evidence that seed failures are more spatially synchronized than mast peaks, indicating that regional coherence in seed production is structured primarily by reproductive failure. Among-species synchrony was localized. This suggests that in temperate forests, mobile seed consumers are unlikely to experience coordinated starvation–satiation cycles, in contrast to highly synchronous tropical dipterocarp systems. From an applied perspective, failure years affect seed availability over broad regions, limiting sourcing options for afforestation and restoration, and underscoring the value of spatially explicit masting forecasting. Because mast peaks and failures differ fundamentally in their food web consequences, our findings highlight the need to better understand and anticipate the ecological impacts of synchronized seed scarcity.